Evaluation of the concentration of inorganic forms of nitrogen and phosphorus under the forest ecosystem of the Čaradický stream - Mária BABOŠOVÁ; Jaroslav NOSKOVIČ (Journal of Central European Agriculture, 2017)
The aim of this study was to evaluate of concentrations of nitrate, ammonium and nitrite nitrogen, total and phosphate phosphorus under the forest ecosystem Čaradice stream during 2005-2010. The average concentration of N-NO3- for the whole of the monitored period was 1.76 mg*dm-3. Its highest average concentrations in all monitored years were generally in the winter. The average concentration of ammonia nitrogen during the whole monitored period was 0.14 mg*dm-3. Minimum average concentrations over the entire observed period were recorded in the winter period and maximum during the summer and autumn periods. The average nitrite nitrogen concentration over the entire monitored period was 0.025 mg*dm-3. Depending on the time of collection, its lowest average concentration was recorded in January and the highest in June and September. The average total phosphorus concentration under the forest ecosystem of the Čadadický stream for the whole monitored period was 0.676 mg*dm-3. Its lowest average value for the whole reporting period was recorded in February and the highest in November. The average concentration of P-PO43- for the whole reference period was 0.203 mg*dm-3. Its lowest average concentration, depending on the collection time, was found in January and the highest in August.